THE EFFECTIVENESS OF WEBSITE-BASED SERVICE TROUGH THE “PELAKU PARADEWI” APPLICATION AT THE POPULATION AND CIVIL REGISTRATION OFFICE OF MOJOKERTO REGENCY - Lucky Arizar; Muhammad Agus Muljanto (SOSIOEDUKASI, 2025)
This study aims to describe and analyze the effectiveness of website-based services through the Pelaku Paradewi application at the Population and Civil Registration Service of Mojokerto Regency. This study uses a descriptive qualitative approach with Duncan's (1973) theory of effectiveness, which includes goal achievement, integration, and adaptation. Data collection techniques included interviews, observation, and documentation, while informant selection techniques used purposive sampling and snowball sampling. Data analysis techniques were carried out through data collection, data condensation, data display, and conclusion drawing/verification. The validity test used source, technique, and time triangulation. The results of the study show that the services provided through the Pelaku Paradewi application at the Population and Civil Registration Service of Mojokerto Regency are considered effective. In goal achievement aspect, population document services through the Pelaku Paradewi application are faster, easier, and more efficient. In integration aspect, coordination between the Population and Civil Registration Office and village officials runs well through intensive communication, technical assistance, and clear division of roles. In adaptation aspect, both parties can adjust to the application after training, supported by adequate infrastructure and facilities. Overall, services through the Pelaku Paradewi application are considered effective in improving the quality of population administration services.